Personalized therapy with lenvatinib for progressive radioiodine refractory differentiated thyroid cancer in routine clinical practice - P. O. Rumyantsev; E. V. Borodavina; S. I. Kutukova; E. B. Vasilyeva (Опухоли головы и шеи, 2021)
Among the differentiated forms of thyroid cancer, the least favorable clinical prognosis is observed in radioiodine-refractory differentiated thyroid cancer. The next step in the treatment of such patients is effective and potential toxicity multi-kinase inhibitors. Often, patients with refractory radioiodine thyroid cancer have a high tumor burden, various symptoms and comorbidity; therefore, clinicians may decide to initiate therapy at a reduced starting dose. In a randomized clinical multicenter study 211 higher objective response rate at 24th weeks were observed in the group of patients receiving lenvatinib at a dose of 24 mg per day compared with patients receiving Lenvatinib at a dose of 18 mg per day, while the difference in the incidence of serious adverse events grade 3–4 (SAE) at the 24th week of treatment were insignificant. Real clinical practice differs from randomized clinical trials regarding to the population of patients, their selection for treatment, adherence to drug dosage regimens, follow-ups, etc. In this paper, we analyzed the world and domestic clinical practice of the treatment of radioiod-refractory thyroid cancer and assessed the effect of the starting dose of lenvatinib and the duration of breaks in its administration on the effectiveness and safety of therapy.